Pengaruh Kualitas Produk, Kualitas Layanan, dan Citra Merek Terhadap Loyalitas Melalui Kepuasan - Kasturi, Diana; Suharyati, Suharyati; Nastiti, Heni (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2019)
This research aims to know product quality, service quality, brand image, with satisfaction as intervening variabel toward loyalty. The problem of research is the large amount of batik imports in Indonesia. The sample in this study amounted to 50 users and customers Batik Betawi Terogong products in West Cilandak, South Jakarta. Sampling is done by using Purposive Sampling. This research uses PLS (Partial Least Square). The results of this study showed that product quality variables have significant influence on loyalty but have no significant influence on loyalty through satisfaction. Service quality have no significant influence on loyalty and also have no significant influence on loyalty through satisfaction. Brand image have significant influence on loyalty, but have no significant influence on loyalty through satisfaction and satisfaction have significant influence on loyalty. Therefore it is expected Batik Betawi Terogong can improve product quality, service quality, and brand image and maintain the satisfaction to be created loyalty to customers.